An Esbat among the Quads: An Episode of Witchcraft at Oxford University in the 1920s. (18th June 2018) - Wheeler, Graham
Abstract : This article presents evidence of an attempt to undertake a revival of witchcraft at Oxford University in the 1920s. The students involved in the attempt appear to have been influenced by ideas about witchcraft that were circulating in contemporary British society, including (but not limited to) the theories of Margaret Murray. The episode constitutes an interesting early step in the progress of the modern witchcraft revival. The surviving evidence also highlights how one of the most prestigious of British institutions could play host to overlapping networks of individuals whose occult interests challenged the norms of both traditional Christianity and secular rationalism.